The broad-host-range plasmid pSFA231 isolated from petroleum-contaminated sediment represents a new member of the PromA plasmid family - Li, Xiaobin; Top, Eva M.; Wang, Yafei; Brown, Celeste J.; Yao, Fei; Yang, Shan; Jiang, Yong; Li, Hui (Frontiers in Microbiology, 2015)
A self-transmissible broad-host-range (BHR) plasmid pSFA231 was isolated from petroleum-contaminated sediment in Shen-fu wastewater irrigation zone, China, using the triparental mating exogenous plasmid capture method. Based on its complete sequence the plasmid has a size of 41.5 kb and codes for 50 putative open reading frames (orfs), 28 of which represent genes involved in replication, partitioning and transfer functions of the plasmid. Phylogenetic analysis grouped pSFA231 into the newly defined PromA plasmid family, which currently includes five members. Further comparative genomic analysis shows that pSFA231 shares the common backbone regions with the other PromA plasmids, i.e., genes involved in replication, maintenance and control, and conjugative transfer. Nevertheless, phylogenetic divergence was found in specific gene products. We propose to divide the PromA group into two subgroups, PromA-α (pMRAD02, pSB102) and PromA-β (pMOL98, pIPO2T, pSFA231, pTer331), based on the splits network analysis of the RepA protein. Interestingly, a cluster of hypothetical orfs located between parA and traA of pSFA231 shows high similarity with the corresponding regions on pMOL98, pIPO2T and pTer331, suggesting these hypothetical orfs may represent ‘‘essential’’ plasmid backbone genes for the PromA-β subgroup. Alternatively, they may also be accessory genes that were first acquired and then stayed as the plasmid diverged. Our study increases the available collection of complete genome sequences of BHR plasmids, and since pSFA231 is the only characterized PromA plasmid from China, our findings also enhance our understanding of the genetic diversity of this plasmid group in different parts of the world.